Eradication of Poverty through Community Green Economic Development Utilizing Khas (Government Jurisdiction) Ponds: Lessons Learned from Grameen Motsho (Fisheries) O Pashusampad (Livestock) Foundation (GMPF) in Bangladesh (Global Journal of Human-Social Science, 2014)
Grameen Motsho O Pashusampad (Fisheries and Livestock) Foundation (GMPF)-is a sister organization of Grameen Bank (GB) involves in livestock and fish culture, mobilizing poor people engage
Keywords: community economic development (ced); fish culture and livestock services; and social business